Context mining social responsibility and governance - Arias Arce, Vladimir (2009)
Conceptualise the corporate social role, which is being unsuitably developed by some mining companies under the cliché of corporate social responsability (CRS), what may wel fall as philanthropic action. This means that actions taken imply a strong assitance constituent, in which the company asually takes on an active rol, and the beneficiary population a passive role. This form of addressing CRS denotes the absence of non-corporate political role-players, thus reducing the chance of consolidating feedback processes between the corporate social investiment and interest group involved poditively. Inplementation of existing legal framework overflows the field, laws are wrongly interpreted, evaded and finally not applied, consecuently minig industry goes through wrong paths. An interest –conciliating legal framework is an imperative. The legal institutional framework implemented in the early 90s, proved to be very effective to generate investiment flows, but with serious limitations when facing social and enviromental conflicts.